IKLIM INVESTASI DI INDONESIA PASCA DIUNDANGKANYA UNDANG -UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA - Bunga Deskomala (2022)
Every country in the world is competing to get investors and develop investment both through domestic investment and foreign investment. Investment is very closely related to the economic growth of a country. The better the investment climate of a country, the better its economic growth. The investment climate in a country will reflect the performance of government policies in controlling both the conceptual and operational levels. Thus, the investment climate of a country will be greatly influenced by the regulations in force in that country. Therefore, the government made a new breakthrough by passing the Job Creation Law using the Omnibus law method. The enactment of the Job Creation Law is aimed at increasing the Rate of Investment in Indonesia. This law changes, deletes, or stipulates a lot of new regulations. Changes made to this law include: application of risk-based business licensing; simplification of the basic requirements for Business Licensing; simplification of sector Business Licensing; and simplification of investment requirements. It is hoped that the enactment of the Job Creation Law will increase the Easy of Doing Business rating so that it can actually attract investors.